Peranan Bahan Organik dalam Peningkatan Efisiensi Pupuk Anorganik dan Produksi Kedelai Edamame (Glycine max L. Merill) pada Tanah Subgroup Vertic Epiaquepts Pegok Denpasar - I NYOMAN DIBIA; I WAYAN DANA ATMAJA (Fakultas Pertanian Universitas Udayana, 2017)
Role in Increasing Efficiency Organic Fertilizers Inorganic Fertilizer and Soybean Production Edamame (Glycine max L. Merill) on The Ground in Subgroup Vertic Epiaquepts at Pegok Denpasar. The study entitled